Daya Tahan Terbang Buhun di Tengah Masyarakat Industri Majalaya - Anwar, Ilham Rahman (LP2M ISBI Bandung, 2023)
Terbang Buhun Majalaya is one of the arts that is synonymous with sacredness. The existence of this art cannot be separated from the type of life of the past Sundanese society which is identical to an agrarian society. Along with the times, changes in society in Majalaya city also occurred, especially from an agrarian society to an industrial society. This change resulted in a consequence on the function of the art of terbang buhun from sacred art to entertainment. However, this situation also presents a challenge for the art of terbang buhun to survive. How can the data hold the art of terbang buhun so that it can still live and exist in the community amid the crush of industrialization that occurs. This research tries to reveal the relationship between urban change and the existence of terbang buhun.